PENERAPAN KONSELING BEHAVIORAL DENGAN TEKNIK SELF MANAGEMENT UNTUK MENINGKATKAN KEDISIPLINAN SANTRI DI PONDOK PESANTREN - syukron, zuhdi; Alif, Indah Melani (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
This Paper aims to find out whether the application of behavioral counseling using self management techniques can improve the discipline of santri at the Al-Hijrah Ngawi Islamic boarding school. The next goal is to find out the increase in the discipline of santri before and after being given behavioral counseling by using self management method. In this research are using descriptive-qualitative methods. Data collection tchniques sing interviews, observation, and documentation. Data analysis in this research used includes; data collection, data reduction, verification, and conclusions. The result of this study is the application of behavioral counseling using self management techniques to improve the discipline of Ngawi islamic boarding school santri Al-Hijrah have a positive impact on daily activities at the boarding school. Santri became more disciplined so the learning activities in the boarding school can be carried out smoothly significant obstacles.